The Impact of Time Interval Between First Extubation and Reintubation on Bronchopulmonary Dysplasia or Death in Very Low Birth Weight Infants - Li, Jing; Zhang, Jing; Hao, Qingfei; Shen, Ziyun; Du, Yanna; Chen, Haoming; Cheng, Xiuyong (Frontiers in Pediatrics, 2022)
Objective To explore the association between time from first extubation to reintubation and moderate-to-severe bronchopulmonary dysplasia (BPD) or death in very low birth weight infants. Study Design Infants weighing <1,500 g at birth, requiring mechanical ventilation, and undergoing their initial extubation were retrospectively included from January 2014 to December 2021. They were divided into the moderate-to-severe BPD/death group and the comparison group according to the incidence of moderate-to-severe BPD or death. We defined time to reintubation as the time interval between first extubation and reintubation. In a stepwise multivariate logistic regression analysis, we examined the association between time to reintubation and moderate-to-severe BPD/death using different observation windows after initial extubation (24-h intervals). Results A total of 244 infants were recruited, including 57 cases in the moderate-severe BPD/death group and 187 cases in the comparison group, and 93 (38.1%) cases were reintubated at least one time after their first extubation. Univariate analysis showed that reintubation rates within different observation windows in the moderate-to-severe BPD/death group were statistically significantly (p < 0.05) higher than those in the comparison group. Multivariate regression analysis showed that reintubation within observation windows 48 h or 72 h post-extubation was an independent risk factor in moderate-to-severe BPD/death and death, but not moderate-to-severe BPD. When the time window was 48 h, the probability of moderate-to-severe BPD/death [odds ratio (OR): 3.778, 95% confidence interval (CI): 1.293–11.039] or death (OR: 4.734, 95% CI: 1.158–19.354) was highest. While after extending the observation window to include reintubations after 72 h from initial extubation, reintubation was not associated with increased risk of moderate-to-severe BPD and/or death. Conclusions Not all reintubations conferred increased risks of BPD/death. Only reintubation within 72 h from initial extubation was independently associated with increased likelihood of moderate-to-severe BPD/death and death in very low birth weight infants, and reintubation within the first 48 h post-extubation posed the greatest risk.